2015
DOI: 10.1002/hep.27698
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated portal hypertension in germ‐free mice: Function of bacterial flora on the development of mesenteric lymphatic and blood vessels

Abstract: Intestinal bacterial flora may induce splanchnic hemodynamic and histological alterations that are associated with portal hypertension (PH). We hypothesized that experimental PH would be attenuated in the complete absence of intestinal bacteria. We induced prehepatic PH by partial portal vein ligation (PPVL) in germ‐free (GF) or mice colonized with altered Schaedler's flora (ASF). After 2 or 7 days, we performed hemodynamic measurements, including portal pressure (PP) and portosystemic shunts (PSS), and collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 36 publications
2
48
0
Order By: Relevance
“…These apocynin-induced responses were accompanied by reductions in vessel proliferation, VEGF and VEGFR-2 protein levels, and vascular superoxide formation, suggesting that superoxide (perhaps by inactivating NO) contributes to a proangiogenic mechanism that involves VEGF and its receptor VEGFR-2. Studies of CPH in germ-free mice also implicate a role for intestinal bacteria (and/or their products) in the development of portosystemic collaterals and in the genesis of portal hypertension (337).…”
Section: Chronic Portal Hypertensionmentioning
confidence: 98%
“…These apocynin-induced responses were accompanied by reductions in vessel proliferation, VEGF and VEGFR-2 protein levels, and vascular superoxide formation, suggesting that superoxide (perhaps by inactivating NO) contributes to a proangiogenic mechanism that involves VEGF and its receptor VEGFR-2. Studies of CPH in germ-free mice also implicate a role for intestinal bacteria (and/or their products) in the development of portosystemic collaterals and in the genesis of portal hypertension (337).…”
Section: Chronic Portal Hypertensionmentioning
confidence: 98%
“…Germ-free mice that lack intestinal bacteria have relatively lower blood pressure when compared with conventional mice [91] and fecal transplantation from hypertensive human donors to germ-free mice elevates blood pressure in these animals [90], suggesting that the gut flora influences blood pressure. In addition, rat studies and randomized clinical trials suggest that administration of probiotics can reduce blood pressure [92,93].…”
Section: Cardiovascular Disease and Mortalitymentioning
confidence: 99%
“…Modulation of the gut microbiota via the administration of antibiotics and probiotics have shown promising results in hemodynamic changes in clinical studies of portal hypertension . To further delineate the role of the gut microbiota, Moghadamrad et al showed that in an experimental model of portal hypertension induced by partial portal vein ligation, germ‐free mice exhibited attenuated portal pressures compared with colonized mice . The authors observed decreased intestinal vascular and lymphatic vessel formation in germ‐free mice after partial portal vein ligation that may partially explain attenuated portal hypertension from decreased inflow.…”
Section: Gut Microbiota and Liver Diseasementioning
confidence: 99%